Feasibility, tolerability, and effects of exercise-based prehabilitation after neoadjuvant therapy in esophagogastric cancer patients undergoing surgery: an interventional pilot study. Issue 4 (17th September 2020) - Argudo, Núria; Rodó-Pin, Anna; Martínez-Llorens, Juana; Marco, Ester; Visa, Laura; Messaggi-Sartor, Monique; Balañá-Corberó, Anna; Ramón, José M; Rodríguez-Chiaradía, Diego A; Grande, Luis; Pera, Manuel
ABSTRACT: Patients requiring surgery for locally advanced esophagogastric cancer often require neoadjuvant therapy (NAT), which may have a detrimental impact on cardiorespiratory reserve. The aims of this study were to investigate the feasibility and tolerability of a 5-week preoperative high-intensity interval training program after NAT, and to assess the potential effects of the training protocol on exercise capacity, muscle function, and health-related quality of life (HRQL). We prospectively studied consecutive patients with resectable locally advanced esophageal and gastric cancer in whom NAT was planned (chemo- or chemoradiotherapy). Feasibility was assessed with the TELOS (Technological, Economics, Legal, Operational, and Scheduling) components, and data on exercise tolerability (attendance and occurrence of adverse or unexpected events). Exercise capacity was assessed with peak oxygen uptake (VO2peak ) in a cardiopulmonary exercise test at baseline, post-NAT, and following completion of a high-intensity interval exercise training (25 sessions). Changes in muscle strength and HRQL were also assessed. Of 33 recruited subjects (mean age 65 years), 17 received chemoradiotherapy and 16 chemotherapy. All the TELOS components were addressed before starting the intervention; from a total of 17 questions considered as relevant for a successful implementation, seven required specific actions to prevent potential concerns. Patients attended a mean of 19.4 (6.4) exercise sessions. The predefined level of attendance (≥15 sessions of scheduled sessions) was achieved in 27 out of 33 (81.8%) patients. Workload progression was adequate in 24 patients (72.7%). No major adverse events occurred. VO2peak decreased significantly between baseline and post-NAT (19.3 vs. 15.5 mL/Kg/min, P  < 0.05). Exercise led to a significant improvement of VO2peak (15.5 vs. 19.6 mL/kg/min, P  < 0.05). Exercise training was associated with clinically relevant improvements in some domains of HRQL, with the social and role function increasing by 10.5 and 11.6 points, respectively, and appetite loss and fatigue declining by 16 and 10.5, respectively. We conclude that a structured exercise training intervention is feasible and safe following NAT in patients with esophagogastric cancer, and it has positive effects to restore exercise capacity to baseline levels within 5 weeks with some improvements in HRQL.